PENGARUH PERUBAHAN JARAK OBYEK KE FILM TERHADAP PEMBESARAN OBYEK PADA PEMANFAATAN PESAWAT SINAR-X, TYPPE CGR - Souisa, Felda; Ratnawati, Ratnawati; Sudarsana, Balik (BULETIN FISIKA, 2014)
Have performed research of objects in an image magnification radiograph film. In irradating the object is done with two variations within the FFD distance and OFD distance. In radiography magnification sought volue as small as possible in order to approach the size of the original image. Based on the results of the avarage magnification at adistance FFD 60 cm, 80 cm, 100 cm, 120 cm, and 140 cm with aech distance OFD 10 cm, 20 cm, 30 cm, 40 cm and 50 cm, value approaching enlargement most closest original image obtained at a distance of FFD 140 cm with distance OFD 10 cm magnification values obtained 1.08 and for the enlargament of the FFD obtained at a distance of 60 cm with 10 cm spacing value obtained OFD enlargement avarage 1.14 at the change of distance FFD erlargement and OFD redunce distance, the resultion obtained is getting smaller shadows and approached the original picture or vice versa on charge FFD distance and OFD irradiation reduced the object, the greater the enlargement obtained.